EFEKTIVITAS PENGGUNAAN BAHAN AJAR KONSEP SISTEM EKSKRESI PADA MANUSIA DALAM BENTUK E-BOOKLET TERHADAP HASIL BELAJAR SISWA MAN - Aisyatunnisa, Rizkya; Halang, Bunda; Noorhidayati, Noorhidayati (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Learning materials are a set of materials that are arranged coherently, systematically and fully display the competencies that students will master in learning activities, the use of various teaching materials can help in learning, one of which is the E-Booklet. E-booklets that are by the learning concept are expected to grow and optimize student learning outcomes. The purpose of this study was to analyze and describe the effectiveness of the E-Booklet on the Concept of Excretion System in Humans on the affective, cognitive, and psychomotor results of class XI MIPA MAN 3 Banjarmasin. This study used a quasi-experimental quantitative research method where the results showed (1) cognitive learning outcomes of students' products showed that there was an effect of using the Excretory System Concept teaching materials on students XI MIPA MAN 3 Banjarmasin, (2) cognitive learning outcomes processes in the good to very good, (3) the effective learning results of the first and second meetings which were obtained based on the results of observations of students' characteristic behavior and students' social behavior were included in the very good category, (4) the psychomotor learning outcomes of the control class were in the good category while the experimental class was in the very good category.